Engineering Design - Dieter, George (McGraw-Hill Companies, 2012)
Dieter's Engineering Design 4/e represents a major update of this classic textbook for senior design courses. As in previous editions, Engineering Design provides a broader overview of topics than most design texts and contains much more prescriptive guidance on how to carry out design. Dieter focuses on material selection as well as how to implement the design process.